The Islamic Left and the Liberation of Oppressed Societies: A Critical Analysis of Hassan Hanafi's Thoght - Anggraini, Reni Dian (Islamic Thought Review, 2024)
This article examines the concept of the Islamic Left in Hassan Hanafi’s thought and its relevance to the liberation of oppressed societies. Hanafi introduces the Islamic Left as a transformative intellectual framework aimed at addressing the multifaceted crises—political, economic, and social—faced by marginalized societies. He envisions this paradigm as a critical tool for dismantling systemic oppression and fostering societal emancipation. Using a critical literature review of Hanafi’s major works, this study examines the core tenets of the Islamic Left and assesses its applicability in contemporary contexts. Hanafi’s approach emphasizes liberation as a central goal of prophetic religious teachings, aligning social justice with the ethical and spiritual imperatives of Islam. His critique of societal structures highlights the need to challenge economic exploitation, political subjugation, and cultural hegemony. Furthermore, his vision advocates a significant paradigm shift in Islamic thought, urging a move from a theocentric worldview—centered on divine transcendence—to an anthropocentric perspective, which places human agency and dignity at the forefront of social and civilizational struggles. This article contributes to the broader discourse on religion and social justice by demonstrating the relevance of Hanafi’s Islamic Left in contemporary efforts to combat inequality and foster progressive social change. It highlights the enduring significance of liberation theology within modern Islamic intellectual traditions.